Beautiful villain - Kenney, Rebecca ([Gilded monsters], 2024)
Daisy and Gatsby meet again in this erotic romance based on characters from "The Great Gatsby." This time, Gatsby has become wealthy by selling the secret of immortality, and he is no longer the man Daisy once knew. Unable to resist him, she finds herself caught in a world of dark desires, dealing with her new untested powers, and facing an unimaginable threat that will force her to make an impossible choice.